Inovasi Aplikasi Info PBBP2 Untuk Meningkatkan Realisasi Pembayaran Pajak Bumi Dan Banugunan Di Kabupaten Agam - Nofril Astri Putra; Roni Eka Putra (CV. ITTC INDONESIA, 2024)
This research aims to increase the realization of Rural and Urban Land and Building Tax payments in Agam Regency. This type of research is qualitative research. Data collection techniques that use words in descriptive form. Data includes interviews, notes that occur in the field, photographs, personal documents related to research, memos and official records. Data analysis is carried out by descriptive analysis, where after the collected data is processed and then analyzed by giving an interpretation. The results showed that the long span of control over the realization of Land and Building Tax in Agam Regency indicates a continuous and sustainable effort in improving the effectiveness of tax collection and meeting tax revenue targets. With the implementation of the Info PBBP2 application innovation, this span of control is further expanded. The responsive Info PBBP2 application that can be accessed through various platforms allows taxpayers to make tax payments easily and conveniently. They can access billing information, payment history, and make transactions online without having to come to the tax office physically. This reduces administrative barriers and increases convenience for taxpayers in fulfilling their tax obligations.